2013
DOI: 10.1536/ihj.54.382
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Self-Care Is an Independent Risk Factor for Adverse Clinical Outcomes in Japanese Patients With Heart Failure

Abstract: SummarySelf-care is a cornerstone for the successful management of heart failure (HF). The purpose of this study was to examine the impacts of HF self-care on prognosis in Japanese patients with HF. A total of 283 HF outpatients (age 64 ± 14, 70% male, 52% HFrEF) were enrolled. We asked patients to answer about their adhevence to 5 self-care behaviors (medication, eating a low-sodium diet, regular exercise, daily weight check, and treatment seeking behavior). On the basis of the results, we classifi ed patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…This possibility is concerning given that even mild cognitive deficits may interfere with important self-care practices for HF. In a recent study, poor self-care was an independent risk factor for cardiac events and hospitalizations as well as length of hospital stay (21).…”
Section: Fi Gure 3 Cardiac Index and Cerebral Blood Flowmentioning
confidence: 96%
“…This possibility is concerning given that even mild cognitive deficits may interfere with important self-care practices for HF. In a recent study, poor self-care was an independent risk factor for cardiac events and hospitalizations as well as length of hospital stay (21).…”
Section: Fi Gure 3 Cardiac Index and Cerebral Blood Flowmentioning
confidence: 96%
“…Self-care of HF is a multidimensional construct that includes adherence to the treatment regimen (e.g., taking medication as prescribed) and consulting behaviours (e.g., calling the provider in case of shortness of breath) 8 . Several studies have shown that people who perform adequate self-care have better QOL, fewer hospitalization and longer survival [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…7,8) Malnutrition in HF patients causes body fluid accumulation and infection and exacerbates their general physical condition, resulting in a further deterioration in their nutritional status. Patients may be caught in a vicious circle, starting with malnutrition, progressing to cardiac cachexia, and ending with an extremely poor prognosis.…”
mentioning
confidence: 99%